Comparative analysis of actinorhizal nodule and associated soil microorganism diversity and structure in three Alnus species - Tong, Aizi; Liu, Wei; Liu, Xiaoliang; Zhu, Junyi; Zhou, You; Li, Jianhua (Frontiers in Plant Science, 2025)
BackgroundDue to the importance of biological nitrogen fixation in terrestrial ecosystems, actinorhizal symbiosis has attracted more and more attention. Alders (Alnus) are important actinorhizal plants, but little is known about the diversity of symbiotic microbiota in the actinorhizal nodules. In addition, it remains unclear about the influence of the host species and habitats on the microbial community of alder root nodules and rhizospheric soils.MethodsIn this study we sequenced the hyper-variable regions of the 16S rRNA from the root nodules and their rhizosphere soils of three alder species (Alnus mandshurica, A. sibirica, A. japonica) in northeastern China to explore the diversity, composition, network association, and nitrogen cycling pathway of the microbial communities in the actinorhizal nodules and associated soils.ResultsThe results showed that the microbial community α-diversity decreased significantly from the associated soil to the root nodule, and the microbial diversity in the root nodule of A. sibirica was not affected by the habitats. The dominant microbe genus in alder nodules was Frankia, whose abundance was significantly higher than that in associated soil samples. Furthermore, the abundance of Frankia was affected by alder tree species, but not by the habitats. The most significant taxon in the nodules of all the three alders was Frankia genus, which was negatively correlated with other six genera of microbes. The main function of microorganisms in alder nodules is nitrogen fixation, which is not affected by tree species and their habitats.ConclusionThese findings suggest that the host determines the microbial community composition in the root nodule of three alders. This study provides valuable insights into the effects of alder species and habitats on the microbial communities of alder nodules and associated soils.